Pilot Trial of Adoptive Transfer of Chimeric Antigen Receptor–transduced T Cells Targeting EGFRvIII in Patients With Glioblastoma. Issue 4 (May 2019) - Goff, Stephanie L.; Morgan, Richard A.; Yang, James C.; Sherry, Richard M.; Robbins, Paul F.; Restifo, Nicholas P.; Feldman, Steven A.; Lu, Yong-Chen; Lu, Lily; Zheng, Zhili; Xi, Liqiang; Epstein, Monica; et al.
Abstract : A deletion variant of epidermal growth factor receptor ( EGFRvIII ) is a known driver mutation in a subset of primary and secondary glioblastoma multiforme. Adoptive transfer of genetically modified chimeric antigen receptor (CAR) lymphocytes has demonstrated efficacy in hematologic malignancies but is still early in development for solid cancers. The surface expression of the truncated extracellular ligand domain created by EGFRvIII makes it an attractive target for a CAR-based cancer treatment. Patients with recurrent glioblastoma expressing EGFRvIII were enrolled in a dose escalation phase I trial, using a third-generation CAR construct derived from a human antibody. Transduced cells were administered after lymphodepleting chemotherapy and supported posttransfer with intravenous interleukin-2. The dose escalation proceeded at half-log increments from 10 7 to >10 10 cells. Primary endpoints were safety and progression-free survival. Eighteen patients were treated with final infusion products ranging from 6.3×10 6 to 2.6×10 10 anti-EGFRvIII CAR + T cells. Median progression-free survival was 1.3 months (interquartile range: 1.1–1.9), with a single outlier of 12.5 months. Two patients experienced severe hypoxia, including one treatment-related mortality after cell administration at the highest dose level. All patients developed expected transient hematologic toxicities from preparative chemotherapy. Median overall survival was 6.9 months (interquartile range: 2.8–10). Two patients survived over 1 year, and a third patient was alive at 59 months. Persistence of CAR + cells correlated with cell dose, but there were no objective responses. Administration of anti-EGFRvIII CAR-transduced T cells did not demonstrate clinically meaningful effect in patients with glioblastoma multiforme in this phase I pilot trial.